2021
DOI: 10.3389/fpsyt.2021.698147
|View full text |Cite
|
Sign up to set email alerts
|

Conspiratorial Thinking During COVID-19: The Roles of Paranoia, Delusion-Proneness, and Intolerance of Uncertainty

Abstract: The COVID-19 global pandemic has left many feeling a sense of profound uncertainty about their world, safety, and livelihood. Sources espousing misinformation and conspiracy theories frequently offer information that can help make sense of this uncertainty. Individuals high in intolerance of uncertainty (IU) may be particularly impacted by the impoverished epistemic environment and may thus be more drawn to conspiratorial thinking (CT). In the present work, we show across 2 studies (N = 519) that COVID-19-spec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 62 publications
3
33
0
Order By: Relevance
“…In addition to change in psychotic experiences, the forum users also demonstrated a distrust of governments, and/or discussed COVID-related conspiracy theories. These findings complement the quantitative research that suggests a link between schizotypy, paranoia, and COVID-conspiracies in the general population (Ferreira et al, 2020 ; Kuhn et al, 2021 ; Larsen et al, 2021 ). Studies in diverse samples have suggested that belief in conspiracy theories relates to worsening of mental health (e.g., Chen et al, 2020 ; Leibovitz et al, 2021 ).…”
Section: Discussionsupporting
confidence: 80%
“…In addition to change in psychotic experiences, the forum users also demonstrated a distrust of governments, and/or discussed COVID-related conspiracy theories. These findings complement the quantitative research that suggests a link between schizotypy, paranoia, and COVID-conspiracies in the general population (Ferreira et al, 2020 ; Kuhn et al, 2021 ; Larsen et al, 2021 ). Studies in diverse samples have suggested that belief in conspiracy theories relates to worsening of mental health (e.g., Chen et al, 2020 ; Leibovitz et al, 2021 ).…”
Section: Discussionsupporting
confidence: 80%
“…The COVID-19 crisis is marked by many uncertainties about health and the economy ( Cipolletta and Ortu, 2020 ; Freckelton Qc, 2020 ; Jutzi et al, 2020 ), which can lead individuals to develop or adopt narratives, including conspiracy theories, to make sense of these events ( Wagner-Egger et al, 2011 ), hereby satisfying epistemic needs (i.e., needs for knowledge and certainty). Indeed, higher levels of uncertainty ( Miller, 2020a , b ) and intolerance or avoidance of uncertainty have been related to higher levels of COVID-19 conspiracy beliefs ( Alper et al, 2020 ; Larsen et al, 2021 ) and conspiracy mentality ( Farias and Pilati, 2021 ; Maftei and Holman, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…People scoring high on the Dark Tetrad traits (e.g., Machiavellianism, narcissism, psychopathy, and sadism; Chabrol et al, 2009 ) are more likely to endorse COVID-19 conspiracy theories ( Gligorić et al, 2021 ; Hughes and Machan, 2021 ; Kay, 2020 , 2021b ; Malesza, 2021 ). This may be the result of a tendency of high-scorers to distrust others and suffer from delusions (e.g., believing that other people can read one's mind) ( Kay, 2021a , b ; Larsen et al, 2021 ; Meuer and Imhoff, 2021 ). Indeed, lower interpersonal trust was associated with COVID-19 conspiracy belief in participants from Germany, New Zealand, Portugal, and Serbia ( De Coninck et al, 2021 ; van Mulukom, 2021 ), but not from 15 Latin American countries ( Jovančević and Milićević, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We examined the notifications of MHCA rules and the formation of SMHA and MHRB across the Indian Psychiatric Society South Zone territories. 5 A rapid review of pertinent central and state government notifications and gazettes was Letters to the Editor undertaken from websites up to October 30, 2021, to get information on the formation of MHRB and SMHA.…”
Section: Current Status Of Shma and Mhrb In The South Indian Territorymentioning
confidence: 99%